MANAGEMENT OF CONSOLIDATED PYONEPHROSIS MIMICKING PYELUM STONE IN A PATIENT WITH URETEROLITHOTOMY HISTORY: A CASE REPORT - Akhmad Dikhyak; Andhika, Dimas Panca; Surya, Prima Ardiansah (Indonesian Urological Association, 2026)
Objective: This study presents a case of consolidated pyonephrosis mimicking a pyelum stone. Case(s) Presentation: A 34-year-old woman presented with right flank pain and intermittent fever. NCCT showed severe right hydronephrosis with a 2.5 x 2.0 x 2.8 cm pyelum stone (1300 HU). Supine PCNL was performed, revealing consolidated pus. The stone, found incidentally, was later treated with RIRS. Discussion: Consolidated pyonephrosis may mimic a stone radiologically. Prompt infection control and urinary diversion are critical to prevent sepsis. Conclusion: Multiple procedures were required in atypical stone disease to prevent systemic complications. Keywords: Pyelum stone, consolidated pyonephrosis, infection.